DESIGN AND IMPLEMENTATION OF NODE AND GATEWAY FOR LORA-BASED AIR QUALITY MONITORING SYSTEM - Sutirta, Kelvin
Air quality data is used by DLHK (Department of Environtment and Sanitation) in Bandung City as a foundation for deciding policies and guindance to public. Real time air quality data is required for each sub-district of a city. But these air quality monitoring stations are very expensive and require regular maintenance. Only one air quality monitoring station is present in Bandung City, which is a long far from an ideal situation of 10 air quality monitoring units. Therefore, a low-cost air quality monitoring system become a solution for dealing with areas not covered by monitoring stations. The developed air quality monitoring system consists of 4 layers, such as nodes, gateways, cloud servers, and a graphical user interface (GUI) that can monitor PM2.5, PM10, CO, temperature, and humidity. The workings of the developed system begin with nodes acting as acqusition unit of air quality parameters, gateways acting as links between nodes and cloud servers, cloud servers as data processing components, and a GUI visualizing the results of data processing. The focus of this final project is the design and implementation of the nodes and gateways of the system. The node is made up of two subsystems: the I/O & Control subsystem which serves as the control system, power management, and the node configuration; and the Data Acquisition Unit subsystem which is in charge of using sensors to measure air quality parameters and transmitting the data to the gateway. The gateway consists of 2 subsystems: the I/O & Control subsystem which performs similar duties to the node; and the Access Point which is responsible for obtaining air quality data from the node and transmitting it to the cloud server. Only the Node Communication module, which is responsible for using LoRa communication to send requests to nodes and receive data from nodes, is being worked on as part of the Access Point subsystem. The node and gateway communication systems use AES128 encryption to ensure reliability. The results of the implementation of the final project are hardware nodes and gateways that are able to operate with 2 sources of power: 220 VAC power grid and a 7.4 V battery that can run up to 18 hours with a battery. The node can measure PM2.5, PM10, CO, temperature, and humidity parameters simultaneously. Nodes and gateways can communicate across a distance of up to 500 meters with a data transmission latency of 4,451 seconds. In addition, stress testing on nodes and gateways were run outside for seven days in hot and wet to simulate product durabilty in enviromental conditions.